Commonality of Ethanol and Nicotine Reinforcement and Relapse in Wistar‐Derived UChB Rats: Inhibition by N‐Acetylcysteine. (13th August 2018) - Quintanilla, Maria Elena; Morales, Paola; Ezquer, Fernando; Ezquer, Marcelo; Herrera‐Marschitz, Mario; Israel, Yedy
Abstract : Background: Life expectancy is greatly reduced in individuals presenting alcohol use disorders and chronic smoking. Literature studies suggest that common mechanisms may apply to the chronic use and relapse of both alcohol and nicotine. It is hypothesized that an increased brain oxidative stress and neuroinflammation are involved in perpetuating these conditions and that a common treatment may be considered for both. Methods: Rats bred as high ethanol (EtOH) drinkers (UChB) were allowed chronic access to EtOH solutions and water and were thereafter deprived of EtOH for a prolonged period, subsequently allowing reaccess to EtOH, which leads to marked relapse binge‐like drinking. Separately, EtOH‐naïve animals were chronically administered nicotine intraperitoneally and tested under either a conditioned place preference (CPP) reinstatement condition or allowed a free‐choice drinking of nicotine solutions and water. Oral N ‐acetylcysteine (NAC) (100 mg/kg) was administered daily to the animals to determine its effect on both chronic voluntary EtOH and nicotine intake, on EtOH relapse and nicotine‐CPP reinstatement. Oxidative stress was evaluated in hippocampus as the oxidized/reduced glutathione ratio (GSSG/GSH), and neuroinflammation by glial fibrillary acidic protein (GFAP) immunohistochemistry. Results: Marked increases in hippocampal oxidative stress (GSSG/GSH) and neuroinflammation (astrocyte reactivity, GFAP) were observed after both chronic EtOH and chronic nicotine treatment. Oral NAC administration (i) fully abolished the increased oxidative stress and the neuroinflammation induced by both drugs, (ii) greatly inhibited EtOH intake (70%) and EtOH relapse binge‐like drinking (76%), and (iii) markedly inhibited (90%) voluntary nicotine intake and fully suppressed nicotine‐CPP reinstatement. Conclusions: Data indicate that (i) oxidative stress and neuroinflammation are tightly associated with chronic EtOH and nicotine intake and drug relapse and (ii) NAC inhibits the relapse for both drugs, suggesting that the oral chronic administration of NAC may be of value in the concomitant treatment of alcohol and nicotine use disorders. Abstract : Alcohol‐use disorders are most commonly associated with heavy cigarette smoking. Animals bred as high alcohol consumers also self‐administer nicotine. Both chronic alcohol and nicotine consumption lead to oxidative stress and neuroinflammation which potentiate each other. Studies are presented showing that both chronic ethanol and nicotine intake and their relapse are greatly inhibited or abolished by the oral administration of N‐acetylcysteine, which also abolishes neuroinflammation and oxidative stress. Translational implications are envisaged.